TOWARDS A UNIVERSAL FRAMEWORK FOR SHARIA ECONOMIC LAW IN GLOBAL RESEARCH ZONES: THEORETICAL INSIGHTS FROM ANTARCTICA GOVERNANCE MODELS - Isabel Lopez; Francisco Lopez; Ratu Baurake; Moana Tarema (Yayasan Adra Karima Hubbi, 2025)
The pursuit of a universal framework for Sharia economic law faces complex jurisdictional challenges in transnational and extraterritorial contexts. Antarctica, governed under the Antarctic Treaty System as a demilitarized and non-sovereign research zone, presents a unique legal landscape to explore how Islamic economic principles might operate in legally pluralistic, cooperative environments. This study examines the theoretical viability of implementing Sharia economic law within global research zones, using Antarctica as a conceptual testbed for non-territorial legal harmonization. The research applies a comparative legal methodology, synthesizing principles of international law, Sharia economic jurisprudence (fiqh muamalah), and environmental governance. Key findings highlight shared values between Sharia law and Antarctic governance, including non-exploitative resource management, communal benefit, and equitable stewardship. The absence of territorial sovereignty in Antarctica provides a neutral platform to theorize models of ethical finance and contract law that transcend nation-state limitations. The study concludes that Antarctica’s cooperative governance structure offers valuable theoretical insights for developing a universal, ethically grounded framework for Sharia economic law in transnational zones. This research contributes to debates on global legal pluralism, ethics in frontier economies, and the adaptability of Islamic law in novel legal environments.